2013
DOI: 10.1186/1471-2458-13-597
|View full text |Cite
|
Sign up to set email alerts
|

‘Roll-your-own’ cigarette smoking in South Africa between 2007 and 2010

Abstract: BackgroundThe prevalence of smoking and consumption of cigarettes have decreased in South Africa over the last 20 years. This decrease is a result of comprehensive tobacco control legislation, particularly large cigarette tax increases. However, little attention has been given to the potential use of ‘roll-your-own’ cigarettes as cheaper alternatives, especially among the socio-economically disadvantaged population. This study therefore sought to determine socio-demographic correlates of ‘roll-your-own’ cigare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…5 The prevalence found in this study was slightly lower than the reported national prevalence for tobacco use: 18.1%, 16.9% and 17.6% in 2010, 2011 and 2012, respectively. 16,21,22 However, our result was similar to a report by Waweru et al, 28 which found a smoking prevalence of 15% among adults in Johannesburg, South Africa. In South Africa, the prevalence of smoking was reported to have modestly reduced between 2004 and 2014, from 24% to 20%; however, there was no reduction in the number of smokers, due to population growth.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…5 The prevalence found in this study was slightly lower than the reported national prevalence for tobacco use: 18.1%, 16.9% and 17.6% in 2010, 2011 and 2012, respectively. 16,21,22 However, our result was similar to a report by Waweru et al, 28 which found a smoking prevalence of 15% among adults in Johannesburg, South Africa. In South Africa, the prevalence of smoking was reported to have modestly reduced between 2004 and 2014, from 24% to 20%; however, there was no reduction in the number of smokers, due to population growth.…”
Section: Discussionsupporting
confidence: 91%
“…15 Over the past 20 years, a modest reduction in the prevalence of tobacco use has been documented in South Africa following the implementation of comprehensive tobacco control legislation; the number of smokers, however, remains the same as a result of increase in population. 16,17 Tobacco control legislation includes an increase in cigarette tax, anti-smoking legislation, as well as improved awareness of the dangers of cigarette smoking. [16][17][18] Recently, a smoke-free law was also enacted in South Africa, which allows smoking only in designated smoking areas in workplaces and public places.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In addition, an integrative approach towards taxation of different tobacco products may be necessary to avert or reduce price-minimization strategies, such as switching to relatively cheaper products such as hand rolled cigarettes, as previously noted in South Africa. 20 This study found some striking disparities in smoking among certain population groups. For example, smoking prevalence increased among females with the highest education, but not among their male counterparts.…”
Section: Discussionmentioning
confidence: 65%
“…35 According to a monitoring and evaluation report produced by the Southern Africa Resilience Innovation Lab, School of Health Systems and Public Health, RYO cigarettes pose a greater health risk than factory produced cigarettes due to a difference in weight, diameter, packing density and porosity of the wrapping paper. 36 Studies report that RYO cigarettes require more puffs, and the smoker therefore inhales more smoke per cigarette for a longer period of time, exposing themselves to a wider range of carcinogens and other harmful substances.…”
Section: 34mentioning
confidence: 99%